MANAGEMENT OF THE PALAMPITAN PUBLIC PASSENGER TRANSPORT TERMINAL AT THE TRANSPORT DEPARTMENT OF NORTH HULU SUNGAI REGENCY - HAJI MUKTI RAMADHANI; Riswandi Ahdiat; Siti Salehah (Universitas Dharmawangsa Medan, 2026)
Management is a process of helping to formulate a policy and organizational goals or processes that provide oversight to something involved in the implementation and achievement of goals. Based on initial observations of the management of the Palampitan public passenger car terminal, there are problems, namely, the facilities at the terminal are not supported, the terminal yard is not clean enough, human resources are lacking, and the budget for managing the terminal is very minimal. Based on the above, this study aims to determine the management of the Palampitan public passenger car terminal, inhibiting factors and efforts made in improving the management of the Palampitan public passenger car terminal at the Department of Transportation of North Hulu Sungai Utara.This study used a qualitative research method with a qualitative descriptive research type. Data collection techniques used are interviews, observation, and documentation. Sources of data were taken through the withdrawal of informants by purposive sampling of 10 people. After the data is collected, it is then analyzed using techniques including data reduction, data presentation and verification or drawing conclusions.The results of the study show that the management of thePalampitan public passenger car terminal cannot be said to be good. Indicators that are not good can be seen from indicators of program accuracy, maintenance of public facilities and supporting facilities, officers working according to their duties, officers working according to their responsibilities, working with discipline, efficient implementation, monitoring of terminal orderliness, and the monitoring system at the terminal. In addition, the driving factor for the management of the Palampitan public passenger car terminal is data accuracy and non-overlapping. The inhibiting factors are the lack of human resources, the lack of budget for the terminal, the inadequate facilities and the lack of supervision. Efforts have been made to improve terminal maintenance which has not been maximized and to increase the budget to maximize terminal facilities.In order to optimize the management of the terminal, it is expected that the head of the Department of Transportation should provide guidance to subordinates so that they can work more responsibly, be disciplined and pay more attention to the Palampitan public passenger car terminal. The head of the transportation and terminal section needs to carry out monitoring, evaluation and reporting of activities to ensure that the implementation of activities at the terminal stays on track according to program planning. For the driver to pay more attention to his service, especially in terms of bringing city transportation and pay attention to the safety of passengers.Keywords: The Palampitan Public Passenger Transport Terminal, The Transport Department